Mathematical studies : course companion - Bedding, Stephen; International Baccalaureate Organization (New York : Oxford University Press, 2007)
Offers resources for the mathematics course of the International Baccalaureate Diploma Programme, including coverage of using a graphic display calculator, exercises, examples, and sample exam questions, and advice on the internal assessment project.
Includes index.
Adult
Keywords: International baccalaureate -- Study guides; Mathematics -- Study and teaching (Secondary); International baccalaureate -- Study guides; Mathematics -- Study and teaching